2018
DOI: 10.1080/02670844.2016.1274097
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic modifications of PVDF membranes via swift heavy ion irradiations

Abstract: The paper presents the hydrophilic modification of polyvinylidene fluoride (PVDF) membranes under swift heavy ion (SHI) irradiation. The research work included the irradiation of PVDF membranes of 9 μm thicknesses with 50 MeV Ni ions at fluences of 1 × 10 13 and 5 × 10 13 ion cm −2 . The pristine and irradiated membranes have been investigated by means of Fourier transform infrared spectroscopy, atomic force microscopy, scanning electron microscope and water contact angle measurement. It is observed that poros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The results show that Fe 8e14 -Sb 2 Te 3 /Ti has increased hydrophilicity compared to that of Sb 2 Te 3 /Ti. From Figure S14, it can be shown that as the irradiation dose increases, the hydrophilicity of the catalyst increases in turn . The water molecules are prone to experience adsorption on the defect sites. , In addition, H 2 O may strongly interact with unbonded Sb and Te atoms, which also contributes to the hydrophilicity of irradiated samples .…”
Section: Resultsmentioning
confidence: 99%
“…The results show that Fe 8e14 -Sb 2 Te 3 /Ti has increased hydrophilicity compared to that of Sb 2 Te 3 /Ti. From Figure S14, it can be shown that as the irradiation dose increases, the hydrophilicity of the catalyst increases in turn . The water molecules are prone to experience adsorption on the defect sites. , In addition, H 2 O may strongly interact with unbonded Sb and Te atoms, which also contributes to the hydrophilicity of irradiated samples .…”
Section: Resultsmentioning
confidence: 99%
“…Many effective strategies, for example blending, radiation grafting, surface coating, swift heavy ion irradiation, surface depositing, and three‐dimensional printing, have been applied to modify the PVDF material . Many researchers have reported modified PVDF films with antifouling, pH responsive, wetting resistance, piezoelectric, and hydrophilic performance . To yield some new characteristics, many studies are still ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in water treatment, distillation, electrical energy storage, composite film preparation, fuel cells and batteries, gas absorption and desorption, chemical pulse cleaning, and so on. Many effective strategies, for example blending, radiation grafting, surface coating, swift heavy ion irradiation, surface depositing, and three‐dimensional printing, have been applied to modify the PVDF material . Many researchers have reported modified PVDF films with antifouling, pH responsive, wetting resistance, piezoelectric, and hydrophilic performance .…”
Section: Introductionmentioning
confidence: 99%